Graduate Entrepreneurship, ADHD and the Creation of Young Entrepreneurs: Is There a Need to Rethink? - Kirby, David A.; Honeywood, Danielle (Senate Hall, 2007)
Around the world education institutions are being charged with the creation of more student entrepreneurs. One group of young people whom, like many successful entrepreneurs, do not normally succeed in the formal education system are those with Attention Deficiency and Hyperactivity Disorder (ADHD). Often regarded as problem cases and/or nuisances, such young people frequently display many of the characteristics traditionally associated with entrepreneurs. The study uses the Durham University General Entrepreneurial Tendency (GET) Test and Crane's Alert Scale of Cognitive Style Test to determine the entrepreneurial tendencies and brain preferences, respectively, of 30 young people with ADHD and 30 students of Management. It discovers that they are more entrepreneurial than the traditional university student and, like successful entrepreneurs, have a right-brain learning preference. The implications of the findings are considered for the creation of student entrepreneurs and entrepreneurship education.
Keywords: graduate|ADHD|entrepreneurship development